Cyclical movements in unemployment and informality in developing countries - Mariano Bosch; William F. Maloney (Institute for the Study of Labor (IZA), 2008)
This paper analyzes the cyclical properties of worker flows in Brazil and Mexico, two important developing countries with large unregulated or informal sectors. It generates three stylized facts that are critical to the accurate modeling of the sector and which suggest the need to rethink the approaches to date. First, the unemployment rate is countercyclical essentially because job separations of informal workers increase dramatically in recessions. Second, the share of formal employment is countercyclical because of the difficulty of finding formal jobs from inactivity, unemployment and other informal jobs during recessions rather than because of increased separation from formal jobs. Third, flows from formality into informality are not countercyclical, but, if anything, pro-cyclical. Together, these challenge the conventional wisdom that has guided the modeling the sector that informal workers are primarily those rationed out of the formal labor market. They also offer a new synthesis of the mechanics of the cyclical adjustment process. Finally, the paper offers estimates of the moments of worker flows series that are needed for calibration.
urn:nbn:de:101:1-2008060591
Keywords: J41; 330; Gross worker flows; labor market dynamics; informality; developing countries; Arbeitsmobilität; Informeller Sektor; Konjunkturelle Arbeitslosigkeit; Dualökonomie; Sektorale Beschäftigungsstruktur; Brasilien; Mexiko